Rare Incidence of Congestive Heart Failure in Gastrointestinal Stromal Tumor and Other Sarcoma Patients Receiving Imatinib Mesylate (IM) - Trent, Jonathan C. (Cancer, 2010)
BACKGROUND: We sought to determine the incidence and severity of cardiovascular toxicity due to imatinib mesylate(IM) in GIST and other sarcoma patients, and to explore cardiotoxicity due to IM using cell culture and in vitro models. METHODS: To determine the incidence and significance of serious cardiac adverse events in GIST and other sarcoma patients receiving IM, we performed a retrospective analysis of 219 consecutive patients treated with IM. In vitro studies of IM on cultured cardiomyocytes and biochemical studies of cardiac lysates from mice treated with IM were performed to define the potential cardiotoxic effects of IM. RESULTS: Grade III or IV potentially cardiotoxic adverse events (mostly edema or effusions) occurred in 8.2% of patients, were manageable with medical therapy, and infrequently required dose reduction or discontinuation of IM. Arrhythmias, acute coronary syndromes, or heart failure were uncommon, occurring in less than 1% of treated patients. However, administration of imatinib in a mouse model system resulted in inhibition of activation of protein kinases that are known to be important in the cardiac stress response. CONCLUSION: We conclude that imatinib is an uncommon cause of cardiotoxicity and that the cardiovascular adverse events that occur are manageable when recognized and treated. Nevertheless, our pre-clinical findings suggest that imatinib remains a potential cardiotoxin. Furthermore the cardiac consequences of long-term imatinib therapy remain unknown. We therefore recommend treatment of risk factors for cardiovascular disease in imatinib treated patients in accord with the American Heart Association guidelines for the prevention and treatment of heart failure.